The Relationship Between low Adult Literacy Levels and Aboriginal Family and Community Engagement in Educational Decision Making - Ratcliffe, Ruth; Boughton, Bob (Australian and International Journal of Rural Education, 2019)
This article draws on work with communities in the rural and remote towns of Brewarrina, Wilcannia and Enngonia, New South Wales (NSW) to explore the relationship between low adult literacy levels and the continuing alienation of Aboriginal communities from educational decision making. Building on the analysis of community-school relations conducted by scholars such as Jay Phillips, Allan Luke and Kevin Lowe, we contend that it is exceedingly difficult to address the problems which prevent more productive relationships between communities and schools in widespread and sustainable ways, without also addressing the problem of low adult literacy. Communities who have participated in the Yes, I Can! Aboriginal Adult Literacy Campaign help us to understand a number of important issues, including, the extent of disenfranchisement that is associated with inadequate adult literacy, the enormity of the challenges faced by previously low-literate and disengaged people to re-engage in community life, the additional pressures placed on literate members of the community when many people have minimal literacy, and the relationship between low rates of adult literacy and the persistence of deficit thinking on the part of schools.